Electric-fish-inspired actuator with integrated energy-storage function. (February 2020) - Weng, Mingcen; Duan, Yimin; Zhou, Peidi; Huang, Feng; Zhang, Wei; Chen, Luzhuo
Abstract: Actuators are energy-conversion devices, which convert different types of energy ( e.g. light, electricity and heat) into mechanical energy and exhibit shape-deformations. They have significant applications in artificial muscles, soft robot, etc . However, most of the actuators only possess shape-deformation function, lacking in the integration of multi-functions, which is against the integration of smart devices and miniaturization of soft robots. In nature, electric fishes can produce electricity. Their myogenic electrocytes are formed from skeletal muscles. Here, inspired by the multiple functions of muscle or myogenic cells in the electric fish, we propose a multi-functional actuator with integrated energy-storage function based on graphite/polyaniline (GP) paper-like composites. After in situ polymerization, the surfaces of graphite nanosheets are surrounded by polyaniline nanoparticles. The GP paper-based actuator exhibits advantages of ultralow driving voltage (≤2.5 V), large bending curvature (1.03 cm −1 ) and long cycling life (>10000 cycles). Meanwhile, the GP paper-based supercapacitor shows great electrochemical performances with areal specific capacitance of 402.5 mF cm −2 and capacitance retention of 79.1% after 10000 cycles. According to these characteristics, a multi-functional actuator integrated with supercapacitor units is constructed, which mimics not only the shape-deformation function of muscle cells, but also the discharging property of myogenic electrocytes in electric fish. We believe this study will open a new way to the design and applications of wearable devices, multi-functional artificial muscles and integrated soft robots. Graphical abstract: Image 1 Highlights: Inspired by electric fishes, an actuator with energy-storage function is proposed. Actuator shows a large bending actuation when driven by an ultralow driving voltage. Supercapacitor unit shows great electrochemical performances. Multi-functional actuators can be used as artificial muscles and power supply units.